PREVALENCE OF POULTRY DISEASES IN DISTRICT CHAKWAL AND THEIR INTERACTION WITH MYCOTOXICOSIS: 2. EFFECTS OF SEASON AND FEED - A. W. Yunus; M. K. Nasir; Tariq Aziz; J. Böhm (Journal of Animal and Plant Sciences, 2009)
Relationship of season and type of feed with disease incidence and interaction of these diseases with mycotoxicosis in layers and broiler flocks in district Chakwal, were investigated. These investigations were based on postmortem examination of birds submitted to the Poultry Production Institute, Chakwal, during 2003-04. To see the effects of seasonality, year long duration was divided into four equal parts, starting from January. Source of poultry feed, being important influencing factor on disease incidence, was included in the analysis as farmers of this area used feed marketed by 20 different commercial millers. Coccidiosis, E. coli infections, New Castle disease (ND), Hydropericardium Syndrome (HPS), mycotoxicosis, ascites, enteritis, and typhoid were among those being highly influenced by feed factors. Incidence of all the respiratory diseases in home-mix feed group and combined incidence of these diseases in commercial feeds was statistically similar (22.3 vs. 27.8%). But, incidence of coccidiosis, enteritis, and mycotoxicosis which are usually thought to be highly influenced by feed factors was low in home-mix feeds as compared to their total share in commercial feeds (16.7, 0.0, and 0.0% vs. 21.0, 2.3, and 3.9%, respectively). However, as generally envisaged, incidence of ascites was 16.7% in home-mix feeds which is very high as compared to 3.0% combined incidence of the problem in all commercial feeds. In broilers, the incidence of coccidiosis, E. coli infections, and coryza was equally distributed in all the months. Approximately half of the HPS, and ND outbreaks were noted during Jul-Sep. More than half of the total Chromic Respiratory Disease (CRD) cases were seen during April to June, while most of the (IB) cases (37%) were noted during Jan-Mar. In layers, approximately half of the coryza and one third of the CRD outbreaks were encountered in Apr-Jun. However, most of IB cases (72.8%) were observed during Jul-Sep (monsoon) and Oct-Dec. Newcastle disease was mostly seen during Jul-Sep in layers, and had a high seasonal correlation with mycotoxicosis both in broilers and layers (0.8 and 0.6, respectively). Effects of seasonality elicited higher incidence of mycotoxicosis, ND, and IB during monsoon. On the basis of overall low disease incidence six months, from October to March, seemed to be comparatively safer for both broilers ad layers due to overall lower disease incidence.
Keywords: Mycotoxicosis; Coccidiosis; New Castle disease; Prevalence